A new operation on soft sets: extended symmetric difference of soft sets - Stojanović, Nenad S. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Molodtsov introduced the concept of soft sets as a new mathematical tool for dealing with problems containing uncertainties. In the literature, different kinds of operations of soft sets are defined and used in theory and applications. Methods: This study is based on the paper "A New Operation on Soft Sets: Extended Difference of Soft Sets" by Sezgin, Ahmad and Mehmood [Journal of New Theory 27 (2019) 33-42].Results: In this paper, we define a new operation on soft sets, called extended symmetric difference and investigate its relationship between extended symmetric difference and restricted symmetric difference and some other operations of soft sets.Conclusion: The author believes that the obtained results represent a significant improvement of many known results in the existing literature.
Keywords: soft sets; intersection; union; difference; extended symmetric difference